SYNTHESIS AND INVESTIGATIONS OF NEW LIQUID-CRYSTALLINE COMPOUNDS BY COMBINATION OF THE PYRAMIDIC TRIBENZOCYCLONONENE UNIT AND CALAMITIC STRUCTURAL UNITS - BUDIG, H; DIELE, S; GORING, P; PASCHKE, R; SAUER, C; TSCHIERSKE, C (Perkin transactions. 2, 1995)
Novel liquid crystalline compounds, which consist of five or six calamitic 4-cyanobiphenyl, all-trans-bicyclohexyl or 2-alkyl-5-phenyl-1,3,4-thiadiazole units covalently linked by spacers of different length with a bowl-shaped central core (2,3,7,8,12,13-hexa-substituted 10,15-dihydro-5H-tribenzo[a,d,g]cyclononene derivatives) have been synthesized and their phase behaviour was investigated by polarizing microscopy, differential scanning calorimetry and X-ray diffraction. Depending on the spacer length, these compounds exhibit either columnar or lamellar (smectic) mesophases. Some of the new compounds form stable monolayers at the air-water-interface. The force-area isotherms of the thiadiazole derivatives have been recorded and it was found that the films consist of densely packed phenylthiadiazole cores with the carboxylate groups at the tribenzocyclononene unit acting as hydrophilic groups.